The Influence Of Brand Awareness And Lifestyle On Fashion Thrifting Purchasing Decisions With Interest As An Intervening Variable (Case Study On Live Shopee Gallerydna) - Dwi Besti Rahayuningtyas; Budi Santoso; Amalina Maryam Zakiyyah (UNIVED Press, 2026)
This study aims to analyze the influence of brand awareness and lifestyle on purchasing decisions for fashion thrifting, with purchase intention as an intervening variable, among Shopee Live GalleryDNA consumers. A quantitative method with a descriptive-verificative approach was employed, involving 140 respondents selected purposively from 30,000 followers of the Shopee GalleryDNA account. Data was analyzed using Structural Equation Modeling (SEM) via Smart PLS 4.0. The findings reveal that lifestyle significantly influences purchase intention and purchasing decisions, while brand awareness has a significant direct effect on both purchase intention and purchasing decisions. Purchase intention significantly affects purchasing decisions but does not significantly mediate the effects of brand awareness and lifestyle. These results indicate that the direct influence of the independent variables is stronger than the mediated effect. Practically, the findings provide insights for developing marketing strategies focused on consistent brand image and lifestyle alignment within live streaming e-commerce platforms.